GLOBAL RELIEF OF THE EARTH'S SURFACE AS A COMPONENT OF THE TERRESTRIAL ENERGY BALANCE - Ivanov S.S. (My University, 1988)
There has recently been a great increase in interest in the origin of global relief of the earth and in elucidating the patterns of its development. In the present paper we attempt to approach the problem from an energy viewpoint. We consider how energy is transferred from the solid earth to the outer spheres. The conduction channel is limited in the energy quantity it can transport and has a very large inertia. As a result, the earth can respond to changes in the rate of energy flow from the interior mainly by changes in convective transport, principally rifting. To summarize, the relief constitutes an additional component of the overall energy balance of the solid earth that regulates the radiation of its energy into space. It follows that the potential energy of the masses making up the relief is the main characteristic governing the evolution of the relief over time. We thus find that the energy approach to the analysis of successive states of the earth's surface is very useful in the theoretical study of relief generation.